Multiple roles of extracellular polymeric substance in nitrobenzene reduction by nano-sized zero-valent iron in water and their mechanism. Issue 1 (2nd January 2022) - Peng, Yuanming; Mu, Yunsong; Chen, Anwei; Shao, Jihai; Peng, Liang; Zeng, Qingru; Luo, Si
ABSTRACT: Extracellular polymeric substance (EPS) is secreted by many organisms and makes up a significant constituent of natural organic matter in the environment. However, nothing is known about EPS's role in the reduction of pollutants by nano-sized zero-valent iron (NZVI). This research showed that the degradation kinetics of nitrobenzene (NB) by NZVI with EPS (0.0272 ± 0.006 min −1 ) were 2.27 times lower than that without EPS (0.0618 ± 0.006 min −1 ) in the first cycle, mainly due to competition for reactive sites on the NZVI surface and the complexation of EPS with Fe(II) and Fe(III). In the second and third cycle, the degradation kinetics of NB by NZVI alone decreased obviously, while those in the presence of EPS were preserved or accelerated. Comparative studies with a quinine model compound indicated that EPS did not function as the electron shuttle to transmit electrons effectively. X-ray photoelectron spectroscopy, scanning electron microscopy and X-ray diffraction results suggested that EPS could prevent the oxidation of NZVI and even expose more effective sites on the NZVI surface, thus leading to the preservation or enhancement of NZVI reactivity in the second and third NB degradation cycles. Moreover, we found that EPS also provided colloidal stability to NZVI particles, either by steric mechanisms or electrostatic repulsion. These results indicate that EPS can play an important role in the prolongation of NZVI reactivity during standing application. GRAPHICAL ABSTRACT: UF0001